Erinacine A-enriched Hericium erinaceus mycelium ameliorates Alzheimer's disease-related pathologies in APPswe/PS1dE9 transgenic mice. Issue 1 (December 2016) - Tsai-Teng, Tzeng; Chin-Chu, Chen; Li-Ya, Lee; Wan-Ping, Chen; Chung-Kuang, Lu; Chien-Chang, Shen; Chi-Ying, Huang; Chien-Chih, Chen; Shiao, Young-Ji
Abstract Background The fruiting body ofHericium erinaceus has been demonstrated to possess anti-dementia activity in mouse model of Alzheimer's disease and people with mild cognitive impairment. However, the therapeutic potential ofHericium erinaceus mycelia on Alzheimer's disease remains unclear. In this study, the effects of erinacine A-enrichedHericium erinaceus mycelia (HE-My) on the pathological changes in APPswe/PS1dE9 transgenic mouse model of Alzheimer's disease are studied. Results After a 30 day oral administration to 5 month-old female APPswe/PS1dE9 transgenic mice, we found that HE-My and its ethanol extracts (HE-Et) attenuated cerebral Aβ plaque burden. It's worth noting that the attenuated portion of a plaque is the non-compact structure. The level of insulin-degrading enzyme was elevated by both HE-My and HE-Et in cerebral cortex. On the other hand, the number of plaque-activated microglia and astrocytes in cerebral cortex and hippocampus were diminished, the ratio of nerve growth factor (NGF) to NGF precursor (proNGF) was increased and hippocampal neurogenesis was promoted after these administrations. All the mentioned benefits of these administrations may therefore improve the declined activity of daily living skill in APPswe/PS1dE9 transgenic mice. Conclusions These results highlight the therapeutic potential of HE-My and HE-Et on Alzheimer's disease. Therefore, the effective components of HE-My and HE-Et are worth to be developed to become a therapeutic drug for Alzheimer's disease.